2010
DOI: 10.1139/t09-096
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of T-bar penetrometer tests at shallow embedment and in very soft soils

Abstract: The cylindrical T-bar penetrometer was developed for profiling the undrained strength of soft soils in the centrifuge and is now a widely-used offshore site investigation tool. The conventional interpretation of the T-bar test is to convert the measured penetration resistance to soil strength using a single bearing factor associated with steady flow of soil around the bar. This paper describes a new analysis for the interpretation of T-bar penetrometer tests at shallow embedment and in soft soils, which is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(44 citation statements)
references
References 11 publications
3
37
0
Order By: Relevance
“…This not only allows the fully remoulded soil strength to be quantified, but provides a basis for 0 0·0 0·2 0·4 0·6 0·8 1·0 0·0 0·2 0·4 0·6 0·8 1·0 1·2 Experience with a dual pore pressure element piezoball Colreavy, O'Loughlin and Randolph making corrections to the net resistance, accounting for changes in soil buoyancy and load cell changes associated with the changing acceleration field in the centrifuge (Sahdi et al, 2014;White et al, 2010). Typical piezoball and T-bar cyclic remoulding data are provided in Figure 6.…”
Section: Cyclic Remoulding Testsmentioning
confidence: 99%
“…This not only allows the fully remoulded soil strength to be quantified, but provides a basis for 0 0·0 0·2 0·4 0·6 0·8 1·0 0·0 0·2 0·4 0·6 0·8 1·0 1·2 Experience with a dual pore pressure element piezoball Colreavy, O'Loughlin and Randolph making corrections to the net resistance, accounting for changes in soil buoyancy and load cell changes associated with the changing acceleration field in the centrifuge (Sahdi et al, 2014;White et al, 2010). Typical piezoball and T-bar cyclic remoulding data are provided in Figure 6.…”
Section: Cyclic Remoulding Testsmentioning
confidence: 99%
“…Merifield et al, 2009;White et al, 2010;Chatterjee et al, 2012;Zhou et al, 2013). An alternative approach to derive this multiplier directly, is to consider the work required to lift the soil that is displaced by the incrementally advancing ball.…”
Section: Experimental Procedures Preparation Of Clay Specimenmentioning
confidence: 99%
“…This is critical for the design of almost all shallowly embedded offshore infrastructure (Puech et al, 2010) including subsea pipelines, steel catenary risers and mudmats. Large-deformation finite-element (LDFE) analyses on a T-bar (White et al, 2010;Tho et al, 2012), spudcan (Hossain et al, 2005) and ball penetrometer (Zhou et al, 2013) have shown that the transition depth from N b-shallow to N b-deep is dependent on the dimensionless strength ratio s u /c9D, where c9 is the effective unit weight of the soil and D is the diameter of the penetrometer. Higher strength ratios are associated with a delay in the transition to a steady N b-deep .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling techniques have been developed to simulate dynamic lay embedment and monitor the development of the pipe embedment with variation of pipe self-weight, horizontal cyclic amplitude and cyclic number (Gaudin and White, 2009). Innovative soil characterization tools, such as the T-bar and ball penetrometer (Randolph et al, 2005), testing procedures, such as the monitoring of load cell drift and cyclic sequences (Randolph and White, 2008a) and results interpretation, such as the treatment of shallow and buoyancy effects in the interpretation of T-bar tests (White et al, 2010a) and the assessment of post-remolding consolidation (White & Hodder 2010) have also greatly benefitted from the outcomes of centrifuge observations.…”
Section: Centrifuge Modelling Of Pipe-soil Interaction Geotechnical Cmentioning
confidence: 99%